Adoption and impact of electronic Human Resource Management: A systematic literature review - El Idrissi, Fadoua El Hajjaji; Benabdelhadi, Abdelhay; Kabaili, Hind (Technium Social Sciences Journal, 2021)
In the era of new technologies and global networking, electronic Human Resource Management (e-HRM) is becoming an increasingly common practice in organizations and a topic of interest to the research community. Through a systematic literature review, this study synthesizes and analyzes research on the adoption and consequences of e-HRM over the last two decades, with the aim of supporting future research in e-HRM. A review of selected references shows that the gains from e-HRM are significant: They can be operational, relational and transformational. Over the years, the debate has shifted from operational to strategic gains. The realization of these benefits is closely linked to the successful implementation of e-HRM. The factors impacting its adoption are multi-dimensional: human, technological, organizational and environmental. Our research examines these determinants in greater detail and highlights the need for more empirical studies to theorize the relationship between adoption factors and the actual gains of e-HRM.